2011
DOI: 10.1111/j.1365-313x.2011.04760.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose synthesis via the FEI2 RLK/SOS5 pathway and CELLULOSE SYNTHASE 5 is required for the structure of seed coat mucilage in Arabidopsis

Abstract: The seeds of Arabidopsis thaliana and many other plants are surrounded by a pectinaceous mucilage that aids in seed hydration and germination. Mucilage is synthesized during seed development within maternally derived seed coat mucilage secretory cells (MSCs), and is released to surround the seed upon imbibition. The FEI1/FEI2 receptor-like kinases and the SOS5 extracellular GPI-anchored protein were shown previously to act on a pathway that regulates the synthesis of cellulose in Arabidopsis roots. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
204
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(216 citation statements)
references
References 49 publications
12
204
0
Order By: Relevance
“…The role of SOS5 in mucilage adherence is more difficult to explain. SOS5 null mutations cause a loss-of-adherence phenotype similar to cesa5-1 seeds, suggesting that SOS5 may regulate mucilage adherence by influencing CESA5 function (Harpaz-Saad et al, 2011). However, the mechanism through which SOS5 could influence CESA5 and/or cellulose biosynthesis is not clear.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…The role of SOS5 in mucilage adherence is more difficult to explain. SOS5 null mutations cause a loss-of-adherence phenotype similar to cesa5-1 seeds, suggesting that SOS5 may regulate mucilage adherence by influencing CESA5 function (Harpaz-Saad et al, 2011). However, the mechanism through which SOS5 could influence CESA5 and/or cellulose biosynthesis is not clear.…”
mentioning
confidence: 92%
“…Recently, CELLULOSE SYNTHASE5 (CESA5) and SOS5 were proposed to facilitate cellulose-mediated mucilage adherence (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011). A simple hypothesis for the role of CESA5 in mucilage adherence is that it synthesizes cellulose, which interacts with the mucilage pectin to mediate adherence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of cellulose, arabinan, and galactan were also found in Arabidopsis seed mucilage (Willats et al, 2001a;Macquet et al, 2007a;Young et al, 2008). Recent studies showed that cellulose plays an adhesive role for the attachment of mucilage pectin to the seed coat epidermal cells (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011). Variations in both mucilage composition and structure have been observed in other plants (Anderson, 1933;Muralikrishna et al, 1987;Naran et al, 2008).…”
mentioning
confidence: 92%
“…In Arabidopsis, FLA3 is involved in microspore development (Li et al, 2010a). Knockout of AtFLA4 resulted in abnormal cell expansion, thinner cell walls, increased sensitivity to salt, and a reduction in the rays of cellulose across the seed mucilage inner layer (Shi et al, 2003;Harpaz-Saad et al, 2011). AtFLA11 and AtFLA12 contribute to stem strength by regulating cellulose deposition and to stem elasticity by affecting the integrity of the cell wall matrix (MacMillan et al, 2010).…”
mentioning
confidence: 99%